Blockchain and smart contracts: a game changer in mediation? - Mak, Charles Ho Wang; Mante, Joseph (Asian journal on mediaton, 2023)
In light of accelerating technological innovation and shifts in dispute resolution paradigms, this article elucidates the transformative potential of blockchain technology and smart contracts in mediation. The paper posits that these advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. The article critically assesses the inherent challenges and argues that overcoming these obstacles necessitates a multi-stakeholder approach, encompassing legislative measures, educational initiatives, and technological enhancements. It ultimately contends that blockchain and smart contracts hold the capacity to significantly reshape the landscape of mediation.
Keywords: Blockchain technology; Dispute resolution; MARD; Mediación; Mediation; Mediação; Médiation; Smart contracts

Arbitrage et modes amiables de règlement des conflits - Clay, Thomas (Recueil Dalloz, 2023)
Le hasard a voulu que la décision qui a été distinguée comme la plus importante de l’année 2023 corresponde à un arrêt annulant une sentence rendue par un tribunal arbitral que présidait l’auteur de ces lignes. Les usages académiques interdisant de commenter un tel arrêt, il sera renvoyé aux innombrables publications dont il a déjà fait l’objet (JCP E 2023. 1061, note D. Mainguy ; JCP 2023. 507, note D. Mouralis ; D. actu. 14 mars 2023, obs. J. Jourdan-Marques ; Rev. arb. 2023. 423, note F.-X. Train ; RTD com. 2023. 582, obs. E. Loquin ; Cah. arb. 2023. 501, note M. Henry ; Gaz. Pal. 16 mai 2023, p. 12, obs. L. Larribère ; JCP 2023. 221, § 4, obs. P. Giraud ; Lexis®PSL, 27 janv. 2023, obs. M.-L. Cartier et A. Meyniel ; Paris Baby Arbitration 2023, n° 59, p. 9, obs. G. Ghedjati et M. Villeneuve ; IA Reporter 12 janv. 2023, obs. L. Bohmer ; Global Arbitration Rev. 13 janv. 2023, obs. A. Ross), ayant même eu les honneurs de l’Agence France Presse (AFP) dans une dépêche du 20 janvier 2023 et… du Canard enchaîné (18 janv. 2023, p. 3). Les commentaires de doctrine sont d’ailleurs très majoritairement critiques sur cet arrêt inattendu, parfois avec des nuances, en dehors d’un seul, celui publié à la Revue de l’arbitrage, qui suit une approche univoque si singulière qu’elle interroge sur les motivations réelles de l’auteur : un professeur de droit ne devrait pas écrire ça. Il n’en reste pas moins que cet arrêt, aussi remarqué qu’il fût, ne sera donc pas commenté dans ces colonnes. Mais, pour que soit moins iconoclaste le paradoxe d’un panorama de droit de l’arbitrage qui n’évoque pas la décision la plus remarquée de l’année en droit de l’arbitrage, encore fallait-il qu’il en fût fait mention dans cet éditorial, lieu d’une licence académique plus libre, sous peine de laisser croire à une auto-censure, voire à une gêne du soussigné, qui, au contraire, assume pleinement d’user de sa liberté d’expression en toutes circonstances.
Keywords: Arbitrage; Arbitration; Convention d'arbitrage; Sentence arbitrale

La distinction entre recours en annulation et exequatur en droit français de l'arbitrage international - Alain, Alex (Université Paris 1, 2023)
S’interroger sur la distinction entre le recours en annulation et exequatur, c'est poser la question du régime juridique applicable à chacun de ces mécanismes de contrôle de la sentence arbitrale. Ces derniers paraissent, par hypothèse, différenciés puisqu’ils relèvent de deux catégories de procédures que le droit français ne confond pas : les voies de recours et l’exequatur. L’application des règles du droit processuel français commande donc en principe de ne pas confondre le recours en annulation, qui est une voie de recours, avec l’exequatur. Or, s’il est bien une notion qui innerve tous les pans du droit français de l’arbitrage international, c’est celle d’« autonomie ». Il en résulte que malgré la référence expresse à des notions bien connues du droit commun - i.e 1’exequatur et la voie de recours pour le recours en annulation -, celles-ci paraissent recevoir une acception spéciale en droit français de l’arbitrage international. Gommant les différences qui séparent traditionnellement les voies de recours de l’exequatur, le droit français de l’arbitrage international semble à bien des égards confondre le recours en annulation et l’exequatur. Émerge ainsi l’idée que les sentences arbitrales font l’objet d’une procédure de contrôle unique. Une confusion certaine entre le recours en annulation et l’exequatur existe en droit français de l'arbitrage international, elle est à l’origine de nombreuses incertitudes. Pour remédier à ce constat, l’étude propose l’application aux sentences arbitrales des règles du droit commun, relatives aux voies de recours et à l’exequatur.
Keywords: Action for annulment; Arbitrage international; Civil Procedure; Contrôle de la sentence arbitrale; Distinction; Droit international privé; Exequatur; International Arbitration Law; Jugements étrangers; Private International law; Procédure civile; Recours en annulation; Voie de recours; Voies d'exécution

Le développement du recours aux modes amiables en matière civile : étude comparée entre la France, les Etats-Unis et le Canada - Watrin, Geoffrey (Université de Strasbourg, 2023)
Darwin disait que « les espèces qui survivent ne sont pas les espèces les plus fortes ou les plus intelligentes, mais celles qui s’adaptent le mieux aux changements ». La justice n’échappe pas à cette règle. Sans cesse confrontée à de nouveaux défis, tels que l’encombrement judiciaire ou la pacification des relations entre les parties, cette dernière va devoir trouver les moyens qui lui permettront de fonctionner en accord avec les besoins de son temps. Les modes amiables de résolution des conflits pourraient bien en faire partie. Implantés de longue date et particulièrement appréciés aux États-Unis et au Canada, ces derniers semblent pour l’heure boudés par les praticiens et les justiciables en France. Le législateur montre néanmoins un intérêt de plus en plus important pour ces méthodes et pour cause : elles ont fait leurs preuves Outre-Atlantique. Dès lors, comment parvenir à les développer au sein de notre système ? C’est la question à laquelle nous essayerons de répondre dans cette thèse.
Keywords: ADR; Canada; Development; Droit comparé; Développement; France; MARC; Mediation; Modes amiables; Médiation; Procédure civile; United States; États-Unis

La mediación y el arbitraje laboral en el Procedimiento concursal: regulación y dificultades aplicativas - Dormido Abril, Julia (Trabajo, Persona, Derecho, Mercado: Revista de Estudios sobre Ciencias del Trabajo y Protección Social, 2023)
La declaración de concurso de una empresa no solo va a afectar al deudor concursado, pues tal calificación también tiene un efecto directo sobre los trabajadores. Sobre todo, si en el seno de un procedimiento concursal, para salvar la continuidad de la actividad empresarial, se decide adoptar alguna medida de reestructuración, tal y como pueden ser las modificaciones sustanciales de las condiciones de trabajo, el traslado, el despido, la suspensión de contratos o la reducción de jornada por causas económicas, técnicas, organizativas o de producción. Las decisiones que sobre cualquier de éstas se tomen pueden dar lugar a conflictos que tienen que solucionarse mientras el proceso judicial sigue su curso. Por ello, el legislador ha incorporado la mediación y el arbitraje en la norma mercantil como vías de solución extrajudicial de tales conflictos. Se trata de una fórmula jurídica no exenta de interrogantes, relacionados en este caso con aspectos como, la norma aplicable a tales mecanismos de solución extrajudicial, la incorporación de la solución al auto o el modo en el que impugnar el acuerdo o el laudo en materia laboral. The declaration of insolvency of a company will not only affect the insolvent debtor, as such a classification also has a direct effect on the employees. Particularly if, within the context of an insolvency procedure, in order to save the continuity of the business activity, it is decided to adopt any restructuring measure, such as substantial modifications to working conditions, relocation, dismissal, suspension of contracts or reduction of working hours for economic, technical, organisational or production reasons. The decisions taken on any of these may give rise to conflicts that have to be resolved while the judicial process is still underway. For this reason, the legislator has incorporated mediation and arbitration into commercial law as a means of extrajudicial settlement of such disputes. This is a legal formula that is not free of questions, related in this case to aspects such as the rule applicable to such out-of-court settlement mechanisms, the incorporation of the solution into the or-der or the way in which to challenge the agreement or award in labour matters.

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Legal Reconstruction of Dispute Settlement Between Importers and Exporters International Law Perspective - Pristha Utama, Wahyu; Tri, Lazarus; Setiyono, Joko (Journal of Xi'an Shiyou University, Natural Sciences Edition, 2023)
Reconstruction of dispute resolution law between importers and exporters from an international law perspective. The purpose of this study is to analyze: 1) How does the law of dispute resolution between importers and exporters perspective international law? 2) How is the implementation of the recommendations of the dispute resolution bodies of the World Trade Organization from an international law perspective? The research method used is normative juridical with a statutory approach, concept approach, and case studies. The results showed that: 1) Import export is a series of company activities that begin with an agreement. The agreement is the result of previous activities carried out by exporters and importers, namely in the form of supply and demand. The agreement is poured into a sales contract which is an agreement between exporters and importers to trade goods in accordance with mutually agreed conditions and each party binds itself to carry out all obligations incurred. 2) The series of processes undertaken in dispute settlement at the WTO consist of 4 processes, including: Mandatory Consultation between disputing parties to reach a settlement approved by the parties, Application for the establishment of a Panel, the Appellate Body, and the implementation and implementation of recommendations and provisions endorsed by the DSB.
Keywords: Dispute Resolution; Exporter; Importer; International Law; Reconstruction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Chronique de jurisprudence de droit de l’arbitrage - Larribère, Lilian (Gazette du Palais, 2023)
Dans la période récente, de nombreuses précisions viennent affermir le régime procédural des recours portés devant le juge français du contrôle. Ainsi, de l’article 1520 du Code de procédure civile qui ne liste que les griefs portant sur la sentence arbitrale elle-même, et qui autorise donc à se prévaloir des moyens d’irrecevabilité de la requête d’exequatur (Cass. 1re civ., 13 avril 2023, n° 21- 50053). Ainsi encore, de l’irrecevabilité du recours en annulation qui n’emporte pas exequatur de la sentence arbitrale (Cass. 1re civ., 7 juin 2023, n° 22-12757). On notera également les arrêts nombreux portant sur le régime de la convention d’arbitrage, et partant de la compétence arbitrale. Enfin, l’arrêt rendu par la Cour de Strasbourg dans l’affaire Semenya (CEDH, 11 juill. 2023, n° 10934/21, Semenya c/ Suisse) montre que le contrôle des droits fondamentaux devra être mené de manière scrupuleuse par le juge de l’annulation, et ce, même si la situation litigieuse ne présentait guère de liens avec les États parties à la CEDH.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Contentieux para-arbitral; Contentieux post-arbitral; Jurisprudence arbitrale

Les modes alternatifs de traitement des conflits familiaux : étude comparative des droits français et ivoirien - Ouattara, Tiégolo Fougniguéta (Université de Bordeaux, 2023)
La famille se fonde sur des liens qui ne sont pas nécessairement rompus par l'existence d'un conflit. De ce fait, la résolution des conflits familiaux nécessite l'usage de méthodes favorisant la restauration des relations familiale ou un vivre ensemble harmonieux entre les membres de la famille. Dans cette perspective, en droit français et ivoirien, les systèmes traditionnels de résolution des conflits familiaux étaient partagés entre la méthode amiable et la méthode judiciaire. En droit français, ce partage s'observe durant la période de l'Ancien régime et la période révolutionnaire. En droit ivoirien, cela s'observe durant la période coloniale. Cependant, dans ces deux ordres juridiques, dans le cadre légal, la méthode amiable a été reléguée au second plan au profit de la méthode judiciaire. Toutefois, ces dernières années, face au besoin de réduire la charge de travail du juge, d'apporter des solutions aux conflits dans des délais raisonnables et d'adapter la résolution des conflits à la conception sociale de la justice, se développent les modes alternatifs. Ceux-ci regroupent un ensemble de mécanismes ayant pour objet la résolution amiable des conflits. Le développement de ces modes varie d'un pays à l'autre. En France, ils font l'objet d'un développement accru. En Côte d'Ivoire leur développement est timide. Néanmoins, des méthodes similaires aux modes alternatifs sont utilisées par le justiciable ivoirien pour la résolution des conflits familiaux, mais dans un cadre informel. Eu égard à l'attachement du justiciable ivoirien à la justice informelle, aussi qualifiée de justice traditionnelle, se manifeste un besoin de sa reconnaissance légale. La justice traditionnelle ivoirienne étant par principe amiable tout comme les modes alternatifs, le développement de ces modes dans la législation familiale ivoirienne pourrait se faire dans le cadre d'une conciliation des règles les régissant avec celles régissant la justice traditionnelle ivoirienne. Mais cette conciliation devrait être faite en tenant compte des limites des modes alternatifs observées grâce à l'expérience française de ces mécanismes et des réalités sociales ivoiriennes. The family is founded on ties that are not necessarily broken by the existence of conflicts. Therefore, resolving family conflicts requires the use of methods that promote the restoration of family relationships or a harmonious living together among family members. In this regard, under French and Ivorian law, traditional systems for resolving family conflicts were divided between the amicable method and the judicial method. In French law, this division can be observed in the periods of the Old Regime and the Revolution. In Ivorian law, this can be observed during the colonial period. However, in both legal systems, the amicable method failed from a legal point of view in favor of the judicial method. This failure was due to the litigant and the legislator. However, in recent years, faced with the need to reduce the judge's workload, provide solutions to conflicts in reasonable timeframes, and adapt conflicts resolution to the social conception of justice, alternative methods of resolution are developed. These comprise a set of mechanisms aimed at amicably resolving conflicts. The development of these methods varies from one country to another. In France, they are subject to increased development. In Côte d'Ivoire, their development is modest. Nevertheless, similar methods to alternative modes are used by Ivorian litigants for the resolution of family conflicts, but in an informal setting. In view of the Ivorian litigants' attachment to informal justice due to the fact that it represents Ivorian traditional justice, there is a need for its legal recognition. Since Ivorian traditional justice is amicable by nature, just like alternative modes, the development of these methods in Ivorian family legislation could take place within the framework of a reconciliation of the rules governing them with those governing Ivorian traditional justice. However, this reconciliation should take into account the limitations of alternative modes observed through the French experience of these mechanisms and ivorian social realities.
Keywords: Alternative modes; Comparative law; Conflicts; Conflits; Côte d'Ivoire; Différends; Disputes; Droit; Droit comparé; Famille; Famille (droit); Family law; France; Justice traditionnelle; Litigation; Litiges; Modes alternatifs; Médiation familiale; Règlement de conflits; Traditional justice

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Revue Justice Actulaités, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

Arbitrabilidade objetiva em contratos administrativos - Cardoso, Paula Butti (Universidade de São Paulo, 2023)
A Lei n° 9.307, de 1996, a Lei de Arbitragem, com a redação que lhe foi dada pela Lei n° 13.129, de 2015, passou a prever expressamente que a Administração Pública direta e indireta poderá utilizar-se da arbitragem para dirimir conflitos relativos a direitos patrimoniais disponíveis. Ultrapassadas as discussões em torno da arbitrabilidade subjetiva, a arbitrabilidade objetiva das disputas envolvendo a administração pública ganha papel de destaque. Divergências a respeito do que seriam os direitos patrimoniais disponíveis da administração pública faz com que a questão seja frequentemente levada ao poder judiciário, em atentado a valores informadores da arbitragem, como a segurança jurídica e a celeridade. Daí a necessidade de se buscar solução para a questão, o que pode ser feito a partir do direito administrativo contemporâneo, que valoriza cada vez mais a atuação consensuada em detrimento da atuação unilateral e impositiva da administração pública. Law No. 9,307, of 1996, the Brazilian Arbitration Law, amended by Law No. 13,129, of 2015, expressly provides that the direct and indirect public administration may use arbitration to resolve conflicts relating to renounceable patrimonial rights. Discussions relating to arbitrability regarding the parties in arbitration have given place to discussions regarding subject-matter arbitrability relating to disputes involving public administration. Different understandings about the renounceable patrimonial rights of the public administration frequently take the discussion to be ruled by judiciary courts, jeopardizing values that inform arbitration, such as legal certainty and celerity. The current scenario demands that a solution to the issue is provided. That can be done based on modern administrative Brazilian law, which increasingly values consensual action rather than unilateral action by public administration.
Keywords: Administrative contract; Administrative law; Arbitrabilidade objetiva; Arbitrability; Arbitrage; Arbitragem; Arbitration; Consensualidade; Consensuality; Contrat administratif; Contrato administrativo; Direito administrativo; Droit administratif

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (2023 TIAC Journal of international dispute settlement inaugural annual conference (TJIDS 2023), 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

L'unification des pratiques de médiation et de conciliation dans les pays membres de l'OHADA - Dah, Sègla Septime (Université de Toulon, 2023)
L’unification des pratiques de médiation et de conciliation s’inscrit dans une démarche centrée sur l’activité du médiateur ou du conciliateur et présente un intérêt double. D’une part, elle forge l’action du médiateur ou du conciliateur en répertoriant les critères afin d’instituer un référentiel qualité. Ce dernier servira à évaluer ses bonnes pratiques du médiateur ou du conciliateur. L’unification desdites pratiques n’entend pas instituer une bonne pratique de la médiation ou de la conciliation. Elle prône pour une identification desdites pratiques afin de constituer un socle commun à l’action et aux prestations de tous les médiateurs des pays membres de l’OHADA. D’autre part, elle est garante du droit à un médiateur compétent et de l’accès à un processus de résolution des conflits de qualité pour une médiation efficace. Le droit à un médiateur compétent et l’accès à un processus de résolution des conflits de qualité sont les deux composantes essentielles du recours effectif à la justice amiable en droit OHADA. Ce recours découle d’un droit de la médiation et de la conciliation qui est en codification dans les pays membres de l’OHADA. Ladite codification est un préalable à cette démarche d’unification. Ainsi, la construction du droit de la médiation et la conciliation doit être accompagnée d’une réelle politique d’unification des pratiques de médiation et de conciliation afin d’inscrire le recours à l’amiable dans l’habitude des justiciables.
Keywords: Amicable settlement; Appeals; Conciliation; Droit de l’amiable; Effectif; Effective; Efficace; Efficient; Evaluation; Justice; Justiciables; Litigants; MARD; Mediation; Médiation; Médiation internationale; Organisation pour l'harmonisation en Afrique du droit des affaires; Quality standards; Recours; Référentiel qualité; Unification; Évaluation

L'incompétence du juge étatique en présence d'une convention d'arbitrage en droit OHADA - Fofana, Modibo Mohamed; Diallo, Hamadi (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2023)
Le droit OHADA de l'arbitrage contient tous les ingrédients pour dissuader l’intervention du juge dans la procédure arbitrale soulevée par les plaideurs les plus récalcitrants. Face aux principes d’autonomie et de force obligatoire de la convention d’arbitrage, l’article 13 de l’Acte uniforme relatif au droit de l’arbitrage pose une obligation d’abstention à la charge du juge étatique à chaque fois qu’il est saisi d’un litige ayant déjà fait l’objet d’une compromission. À moins que la convention d’arbitrage soit manifestement nulle ou manifestement inapplicable, le juge étatique doit s’abstenir de toute intervention. Toutefois, en dépit du principe d’autonomie et de force obligatoire de la convention d’arbitrage, l’absence d’imperium qui caractérise la vie du tribunal arbitral nous amène à relativiser la posture de neutralité dont le juge étatique est contraint d’adopter. Ce dernier, dans le respect de la primauté reconnue à l’arbitre, se verra ponctuellement reconnaître le pouvoir d’assister l’arbitrage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Convention d’arbitrage; Droit OHADA; Incompétence; Juge communautaire; Juge d’appui; Juge étatique

L’intervention du juge étatique dans l’arbitrage de l’Organisation pour l'Harmonisation du Droit des Affaires en Afrique (OHADA) : Une carence normative du droit communautaire - Fofana, Modibo Mohamed; Diallo, Hamadi (International Journal of Strategic Management and Economic Studies (IJSMES), 2023)
Les attributions du juge étatique sont confrontées à un flou juridique qui en résulte l’absence d’un régime juridique claire. A l’issue de cette réflexion, il convient de retenir que l’intervention du juge étatique à l’arbitrage dans l’espace OHADA est une œuvre particulièrement complexe car, si dans l’arbitrage spécifique de la CCJA, Il revient au juge communautaire la charge d’administrer la procédure et d’assurer le suivi durant la phase post-arbitrale, la détermination du juge étatique dans l’arbitrage de droit commun est une opération complexe et ses attributions ne sont pas claires. En effet, le flou lexical entourant l’expression générique désignant le juge étatique, entraîne un morcellement de son champ de compétence. Ce sont ses faiblesses qui justifient que des palliatifs soient proposés en vue de renforcer l’efficacité de l’intervention du juge national et de garantir par la même occasion la sécurité juridique dans l’espace OHADA.
Keywords: Arbitrage; Arbitragem; Arbitration; Juge communautaire; Juge d’appui; Juge étatique; OHADA

La transformation du Système de résolution des conflits entre État hôte et investisseur étranger : la conciliation des intérêts d’acteurs d’un système adaptatif complexe - Deligny Malchair, Marion (Université de Lorraine, 2023)
Les conflits entre État hôtes et investisseurs étrangers occupent, depuis une dizaine d’année le devant de la scène géopolitique. Le questionnement se porte aujourd’hui de façon globale sur l’articulation des méthodes de règlement de conflits particulièrement complexes en raison de leurs implications institutionnelles, juridiques et économiques. Cette thèse se consacre à appréhender le cadre de règlement des conflits d’investissements selon le modèle du système afin de déterminer les conditions nécessaires à la transformation profonde du Système de résolution des différends entre États-hôtes et investisseurs.L’analyse du Système de résolution des différends entre États-hôtes et investisseurs suppose d’abord d’en restituer le contexte historique et d’examiner les bases institutionnelles posées par le système CIRDI, celui-ci étant le fruit d’une idée, la substitution du droit à la force pour la résolution des différends d’investissement : « le paradigme juridictionnel ». Or, si des bases institutionnelles avaient été posées, celles relationnelles ne l’étaient pas. Il s’en suit un usage des mécanismes du Système de résolution des différends entre États-hôtes et investisseurs dans une logique défensive et adversariale. Cependant, la complexification croissante du monde et incidemment du système des investissements, conduit les acteurs de l’investissement à passer d’une logique adversariale à une logique de collaboration et de co-construction pour résoudre les inévitables problématiques auxquelles ils font face : « le paradigme consensuel ».Nous nous interrogeons alors sur les conditions nécessaires à la mise en œuvre de ce nouveau paradigme comme fondement du Système afin d’en provoquer la transformation profonde. L’application de concepts issus du champ d’étude de la complexité et des systèmes adaptatifs complexes permet de conclure que le consensualisme est tout à la fois le résultat et le moyen à mettre en œuvre pour faciliter cette transformation. Seule une démarche holistique, incluant l’ensemble des acteurs dans leur diversité, peut permettre de faire émerger des solutions innovantes à la hauteur des enjeux. Notre proposition est d’utiliser les outils et méthodes du Design Thinking appliqués au droit – le Legal Design- dont la démarche place les parties prenantes, et donc les éléments de culture et de contexte, au cœur du processus de conception de solutions, et susceptible de provoquer un changement dans la dynamique relationnelle des acteurs vers une logique de collaboration. Cette conclusion s’applique aux deux échelles retenues : celle de la transformation globale du Système de résolution des différends entre États-hôtes et investisseurs, et celle des projets d’investissement, dont une gouvernance participative doit être encouragée afin d’en permettre le succès et de permettre de réaliser une des vocations premières du système des investissements qu’est le développement des États d’accueil au bénéfice de leurs communautés. Conflicts between host states and foreign investors have been at the forefront of the geopolitical scene for the past ten years. Now the question is being raised on a global scale concerning the articulation of particularly complex conflict resolution methods because of their institutional, legal and economic implications. This thesis focuses on understanding the framework for resolving investment disputes based on the system model in order to determine which conditions are necessary for the profound transformation of the Dispute Resolution System between host states and investors.Before any analysis of the Dispute Resolution System between host states and investors can be undertaken, it is necessary to provide an insight into the historical context and to examine the institutional foundations of the ICSID system. These are the result of an idea, substituting international law to the use of force for the resolution of investment disputes: “the jurisdictional paradigm”. If institutional foundations were laid, relational ones were not. This resulted in the use of the Dispute Resolution System mechanisms between host states and investors in a defensive and adversarial logic. However, the increasing complexity of the world and, incidentally, of the investment system, has led investment players to move from an adversarial logic to one of collaboration and co-construction in order to resolve the inevitable problems they face: “the consensual paradigm”.We then question the conditions required for the implementation of this new paradigm as the foundation of the System in order to bring about its profound transformation. Applying concepts from the fields of study into complexity and complex adaptive systems leads to the conclusion that consensus constitutes both the outcome and the means to facilitate this transformation. Only a holistic approach, including all the actors involved and their diverse contexts, can make it possible to develop innovative solutions that meet these challenges. Our proposal is to apply Design Thinking tools and methods in a legal context – Legal Design. This approach places stakeholders, and therefore the elements of culture and context, at the heart of the process of designing solutions, and is therefore well suited to bringing about a change in the relational dynamics of the actors towards a logic of collaboration. This conclusion applies to both scales: that of the overall transformation of the Dispute Resolution System between host states and investors and that of investment projects, whose participative governance structure must be recognized as a crucial success factor and a means to support one of the primary purposes of the investment system, which is the development of host states for the benefit of their communities.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Complex Adaptive System; Dispute System Design; Droit international; Foreign investment; Investissements étrangers; Investment Conflits Resolution; Investment Mediation; Legal Design; MARD; Mediación; Mediation; Mediação; Médiation; Médiation d'investissement; Règlement de conflits; Résolution des conflits d'investissement; Système adaptatif complexe

Transparency in international arbitration: balancing the need for openness with the need for confidentiality - Mak, Charles Ho Wang; Rohatgi, Akshita (ACICA review, 2023)
International arbitration is often presented as an efficient and appropriate alternative to domestic court systems for resolving conflicts. For international arbitration to be effective, it is essential that the procedure adopted be open and accountable. This article will discuss the significance of openness in international arbitration and how it may promote justice, foster trust, and avoid corruption and misbehaviour.
Keywords: Corruption; International Arbitration; Justice; Misbehavour; Transparency; Trust

Reconstruction of CCMA Commissioners' Perceptions of Dispute Resolution in South Africa: a multi-perspective approach - Bendeman, H. M. A. (Potchefstroomse Univèrsiteit vir Christelike Hoër Onderwys, 2023)
A reconstruction of CCMA commissioners' perceptions of dispute resolution in South Africa: A multi-perspective approach This study focuses on the problems in the dispute resolution system in South Africa. The aim of this study is to explore the perceptions of commissioners of the Commission for Conciliation, Mediation and Arbitration (CCMA) regarding the capacity of parties to effectively deal with labour .conflict and disputes within the legal framework provided by the Labour Relations Act (LRA) (66/95). This includes an investigation into the reasons for the high referral rate of unfair dismissal cases to the CCMA and the influence of the case-overload on the effective functioning of the disputé resolution system. The · functionalist and conflict theoretical perspectives are used to study the structural aspects of the dispute resolution system and to explore structural strain. The interactionist perspective is used in the methodology of this study to reconstruct the perceptions of a group of CCMA commissioners. This study is predominantly of a qualitative nature and was conducted in an exploratory manner through in-depth interviews and e-mail questionnaires. Dunlop's open systems approach allowed for the conceptualisation of the major dispute resolution components of the labour relations system. T!Je analysis of the transformation of conflict formed the basis for understanding the background, the problem statement, the aims and assumptions of this study. lt was found that the guidelines in Schedule eight of the LRA (66/95) have become the norm for dealing with conflict within an enterprise, creating complex and technical processes for dealing with disputes. However, most of the employers and individual employees do not have the knowledge and skills to operate effectively in the system. This has led to a new type of adversarialism in the individual employment relationship, which is based on rights, rules and power. The very technical nature of the internai conflict resolution mechanisms, the incapacity of the parties and the adversarial nature of the labour relationship have resulted in the high referral rate and consequent problems that the CCMA is experiencing.
Keywords: Afrique du Sud; Arbitrage; Arbitragem; Arbitration; Conciliation; Conflict resolution; Conflits de travail; Dispute settlement; Industrial sociology; Labour dispute; Labour relations; MARD; Mediación; Mediation; Mediação; Médiation; Relations de travail; Règlement des différends; Résolution de conflit; Sociologie industrielle; South Africa

La pérennité du contrat international entre pacta sunt servanda et rebus sic stantibus : réflexions au regard du pouvoir interprétatif de l’arbitre - Bejeoui, Imed (UAEU Law Journal, 2023)

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

The efficacy of commercial arbitration, law and practice Lesotho - Thethe-Chitja, Makabelo (National University of Lesotho, 2023)
The success of commercial arbitration law and practice is achieved as a result of several factors. The purpose of the study was to investigate whether efficacy of commercial arbitration, law and practice in Lesotho is hindered by the legal framework which does not conform to the United Nations Commission Trade Law on International Commercial Arbitration, UNCITRAL Model Law. Examining such other factors as support of the courts and government, the study specifically investigated the impact of lack of education about commercial arbitration for the business community and unregulated arbitrators on the efficacy of the commercial arbitration, law and practice in Lesotho. With the use of the desk reviews and interviews as data collection methods for this study, the evidence obtained has revealed that efficacy of the commercial arbitration, law and practice in Lesotho is hampered by the law which is outdated and inconsistent with the UNCITRAL Model law. As such, support for the mechanism by the courts has been found to be at stake or adversely affected. Lack of support from the government and that of awareness campaigns about the mechanism for the business community have also been noted for constraining the efficacy of the commercial arbitration, law and practice in the country. Further noticeable from the findings include limited commitment from the legal profession and unregulated arbitrators, both of which could have significantly obstructed the mechanism. The study thus concludes that there is an urgent need for law reforms and concerted commitment from the relevant stakeholders to help towards achieving efficacy of the commercial arbitration, law and practice in Lesotho.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration; Lesotho

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

L’immunité des arbitres dans l’arbitrage OHADA - Diallo, Hamadi; Traoré, Abdramane; Traoré, Abdou Bougoury (International Journal of Strategic Management and Economic Studies, 2023)
Cet article, est une contribution à la réflexion sur le statut de l’arbitre en droit OHADA, entamée par plusieurs chercheurs africains, et au centre de laquelle se trouve la problématique de l’immunité en droit de l’arbitrage OHADA. Le débat sur le choix d’un système d’immunité et la définition d’un véritable statut pour l’arbitre est toujours d’actualité. Cet article fait le point global des approches et conceptions sur l’immunité diplomatique des arbitres de la CCJA. En effet, le débat sur la responsabilité touche de façon étroite celui du statut de l’arbitre : la responsabilité étant la résultante d’un statut, cela nous permettra d’aborder la question du statut juridique de l’arbitre en droit OHADA. Dans un contexte où les différentes législations, la jurisprudence ou encore les conventions internationales, n’abordent que très peu le statut de l’arbitre, la détermination des éléments permettant de préciser les contours des devoirs, droits et obligations de l’arbitre, contribuera de façon certaine à mieux appréhender la mission de l’arbitre.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitre; CCJA; Immunité; OHADA

Rights and Obligations of the Parties Against International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The position of international arbitration awards which is different from national arbitration awards and district court decisions causes differences in the rights and obligations of the parties to arbitral awards, especially those relating to legal remedies against awards. The formulation of the problem in this study is how are the rights and obligations of the parties to international arbitral awards in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the study state that the rights possessed by the parties to international arbitral awards in Indonesia are related to legal remedies against decisions, namely corrections to these international arbitral awards. The corrections to the decisions here are not only limited to administrative corrections but also corrections related to the principal international arbitral awards made before the request for execution was registered at the Central Jakarta District Court. While the obligations of the parties to international arbitral awards are to carry out international arbitral awards in good faith.
Keywords: International Arbitration Award; Rights and Obligations

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

L’ouverture du droit d’agir au système des règlements alternatifs des différends en droit OHADA et Camerounais : un procédé séduisant mais d’une efficacité incertaine - Njock, Luc Kevin Leny (Uniform Law Review, 2023)
The processes by which a model of social regulation channels its way of resolving conflicts make the strength of its conflict resolution system. Court justice has lost its exemplary function. The crisis of effectiveness and the crisis of legitimacy that the processual mode of dispute resolution is undergoing in our States, make it a justice system that is considered to have broken down. The need for justice thus directly raises the question of social regulation, the relevant model of social regulation. The call for a ‘right to sue’ open to the system of alternative dispute resolution rather than restrictively to the judiciary to resolve disagreements is the spearhead of the combinatorial approach to the administration of conflicts, the ferment of a plural approach to access to justice. Has Cameroonian law begun to renew its vision of the right to take legal action? Does it renew the dominant classical approach to the system of social regulation? The study notes the global and integral recognition of the alternative dispute resolution system, another, less contentious, way of dealing with disputes, the emergence within the traditional dispute resolution system of a right to amicable dispute resolution, but in an embryonic state. It then poses, in a prospective approach, the need for a unitary and global approach to private justice as challenges to be met to ensure the quality of this form of justice.

L'Arbitrage en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Le recours à l’arbitrage en matière des litiges contractuels entre des parties privées présente des avantages par rapport aux procédures devant les tribunaux. Les avantages de l’arbitrage qui a une valeur particulière en matière contractuelle se multiplient : les arbitres peuvent être choisis en raison de leurs compétences spéciales selon le sujet du contrat; la confidentialité peut être préservée; l’arbitrage peut être utilisé pour régler des questions sur le même sujet ou des sujets semblables mais survenant dans des pays différents, ceci peut présenter l'avantage de régler en une seule fois tous les différends entre les parties, surtout en matière de commerce.
Keywords: Arbitrage; Arbitrage Conventionnel; Arbitrage Judictionnel; Arbitragem; Arbitraje; Arbitration; Commerce; Droit civil; France; Jordanie; Litiges contractuels

La médiation en matière des litiges contractuels - Ismail, Mahmoud (International Multilingual Journal of Science and Technology, 2023)
Dans une économie de plus en plus globalisée, faute d’harmonisation juridique, les parties aux litiges contractuels n’hésitent plus à consulter les forums juridiques pour identifier les pays susceptibles de leur offrir le meilleur niveau de protection. Presque tous les litiges en matière contractuels se prêtent au début des conflits à la médiation. Il arrive souvent que lors d’un litige relatif aux droits contractuels, les parties recourent à la médiation. Cependant, pour pouvoir y recourir de manière utile, il est important d’éluder certains obstacles. Un litige ayant trait à un contrat, soulève des questions complexes de faits et de droit, peut nécessiter des dépenses importantes et exiger la présence de témoins experts. Puisque l’obligation contractuelle émise sera presque toujours un enjeu, un litige ayant trait au commerce, notamment international, commande une connaissance approfondie de la législation sur les objets de transactions, ainsi qu’une expérience des tribunaux qui traitent la plupart du temps de ces questions. En pratique, l’espace de rencontre entre la médiation et les litiges contractuels est le contrat lui-même. Or, le domaine contractuel est le domaine privilégié de la médiation. En réalité, la médiation peut avoir lieu dans les relations liée aux contrats de commerce, dans lequel une dévolution des droits contractuels est prévue. Ce mode alternatif fournit un moyen pour éviter les contentieux judiciaires.
Keywords: Approche comparée; Commerce international; Droit civil; France; Jordanie; Litiges contractuels; Mediation; Médiation

La place contestée de l'arbitrage international en droit de l'investissement - El Issa, Rayyan (Université Paris-Saclay, 2023)
La place de l'arbitrage en droit de l'investissement est discutée. Les réfutations à son encontre grandissent. De nombreuses problématiques édulcorent la définition même de la notion d'investissement. Les controverses doctrinales restent toujours nombreuses et débattues à ce sujet. De même, des doctrines s'affrontent sur la question de savoir s'il faut ou non élaborer un corps de règles cohérentes pour des sentences arbitrales homogènes. L'opposition à l'arbitrage dans le droit de l'investissement se retrouve aussi dans les problématiques liées à l'exequatur des sentences arbitrales liées à l'arbitrage d'investissement dans l'Union européenne. Un manque de soutien apparent au développement de l'arbitrage dans l'Union européenne s'est installé, comme le démontre le récent traité CETA conclu entre l'Union européenne et le Canada. L'arbitrage d'investissement ferait courir le risque d'un recul de la souveraineté. En effet, du fait l'arbitrage d'investissement, les Etats seraient moins incités à légiférer sur des matières pouvant avoir un impact sur l'activité d'une entreprise étrangère, par crainte d'une procédure arbitrale. Un lien délicat apparait alors, entre souveraineté et arbitrage d'investissement. Plusieurs doctrines se sont longtemps affrontées, notamment celle élaborée par Calvo et Drago en Amérique Latine entre 1870 et 1900, proposant de réduire les droits des investisseurs étrangers, face à une doctrine opposée, celle militant pour un standard minimum international de protection des investisseurs étrangers. Or, une renaissance de ces débats apparaît aujourd'hui, avec une problématique liée à la souveraineté de plus en plus ancrée dans les débats liés à l'arbitrage d'investissement. Pourtant, l'arbitrage d'investissement doit être perçu comme une méthode permettant à des investisseurs de bénéficier d'un arbitre indépendant et permettant de « dépolitiser » les contentieux. Mais des Etats admettent de moins en moins que leurs lois établies démocratiquement pour l'intérêt général puissent être contestées par des investisseurs étrangers devant un tribunal arbitral. Des auteurs parlent de « chilling effect », par lequel des Etats n'osent plus légiférer, par crainte de contentieux ultérieurs. De plus en plus d'Etats refusent que leur droit soit remis en cause par des juges privés. Plusieurs questions se posent. Est-il toujours concevable de protéger davantage un investisseur étranger qu'un investisseur national ? Est-il légitime de privilégier des juges privés, plutôt que des juges nationaux pour trancher les litiges en matière d'investissement ? L'utilité de l'arbitrage peut être comprise, dans des pays où la justice étatique est dite « corrompue » ou « biaisée ». En pareille situation, un investisseur étranger est légitime à vouloir saisir un arbitre neutre et indépendant. Mais la légitimité d'avoir recours à l'arbitrage dans des pays développés bénéficiant d'une justice étatique indépendante pose plus de difficultés. Dès lors, faudrait-il limiter l'arbitrage d'investissement aux pays souffrant d'un déficit d'indépendance de justice étatique ? Et donc d'exclure ce mode de règlement des litiges en la matière dans l'Union européenne ? La « politisation » du débat est en pleine renaissance. L'arbitrage d'investissement est un domaine relativement jeune et il convient de se demander s'il s'agit là d'un mode de règlement des litiges adéquat et d'un mode adapté au commerce international en général ? Assistera-t-on prochainement ou assiste-t-on déjà à ce que des auteurs qualifient de « fin de cycle » ? Il s'agit de questions ancrées dans l'actualité, que ce soit en France ou ailleurs dans le monde. The place of arbitration in investment law is discussed. The rebuttals are growing. Many issues water down the very definition of the notion of investment. The doctrinal controversies are still numerous and debated on this subject. Similarly, doctrines clash on the question of whether or not it is necessary to develop a body of coherent rules for homogeneous arbitral awards. The opposition to arbitration in investment law is also found in issues related to the exequatur of arbitral awards related to investment arbitration in the European Union. An apparent lack of support for the development of arbitration in the European Union has set in, as demonstrated by the recent CETA treaty concluded between the European Union and Canada. Investment arbitration would run the risk of a decline in sovereignty. Indeed, because of investment arbitration, States would be less encouraged to legislate on matters that could have an impact on the activity of a foreign company, because of the fear of arbitration proceedings. A delicate link then appears between sovereignty and investment arbitration. Several doctrines have long clashed, in particular the one developed by Calvo and Drago in Latin America between 1870 and 1900, proposing to reduce the rights of foreign investors, in front of an opposing doctrine, that campaigning for a minimum international standard of protection for foreign investors. A revival of these debates is appearing today, with an issue linked to sovereignty increasingly rooted in the debates linked to investment arbitration. However, investment arbitration must be seen as a method allowing investors to benefit from an independent arbitrator and allowing disputes to be “depoliticised”. But states admit less and less that their laws democratically established for the general interest can be challenged by foreign investors before an arbitration tribunal. Authors talk about the “chilling effect”, by which States no longer dare to legislate, because of the fear of subsequent litigation. More and more States refuse to have their rights challenged by private judges. Several questions arise. Is it always conceivable to protect a foreign investor more than a national investor ? Is it legitimate to favor private judges, rather than national judges, to settle investment disputes ? The usefulness of arbitration can be understood in countries where state justice is said to be “corrupt” or “biased”. In such a situation, a foreign investor is legitimate in wanting to seize a neutral and independent arbitrator. But the legitimacy of having recourse to arbitration in developed countries benefiting from independent state justice arouses more difficulties. Therefore, should investment arbitration be limited to countries suffering from a lack of independence of state justice ? And therefore to exclude this method of settling disputes in this area in the European Union ? The “politicization” of the debate is in full revival. Investment arbitration is a relatively young field and it is worth asking whether it is an adequate mode of dispute resolution and a mode suitable for international trade in general ? Will we soon witness or are we already witnessing what some authors describe as the “end of the cycle” ? These are issues rooted in the news, whether in France or elsewhere in the world.
Keywords: Arbitrage; Arbitragem; Arbitration; Contentieux; Contentieux de la concurrence; Droit de l'investissement; Droit et État; Investment Law; Investments; Litigation; Souveraineté; Sovereignty

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Investigation of Investor-State Arbitration Problems in Afghanistan - Nikzad, Nezamuddin; Anwari, Gulaqa (International Journal of Social Science Research and Review, 2023)
The main purpose of this research is to explain and identify the major Investor-State Arbitration (ISA) problems in Afghanistan. Afghanistan's government is committed to providing legal security for the resolution of foreign investment disputes. The dispute resolution system's assessment is very important for foreign investors because they pay special attention to the dispute resolution system and consider it a criterion for their investments. This research will be the first comprehensive study about the Investor-State Arbitration problems in Afghanistan. In the writing of this research, the library method has been used. To extract reasons, laws, books, articles, and reliable scientific sources have been used. Afghanistan is a good market for foreign investment because it has good investment opportunities in different sectors. Foreign investors can choose the easiest and best mechanisms, such as arbitration in their contracts to deal with disputes. But the resolution of foreign investment through arbitration has some problems, and sometimes foreign investors are facing challenges with the settlement of their disputes through arbitration internationally and domestically in Afghanistan.
Keywords: Arbitration; Dispute; Foreign Investment; Investigation in Afghanistan; Problems

La Diplomatie juridique : Défense et illustration du droit français et du droit continental dans le droit global à travers les exemples de la médiation et de l'arbitrage international - Gontier, Jean-Yves (Université Paris-Saclay, 2023)
Dans la conception traditionnelle de la diplomatie, l'action extérieure des États est cantonnée aux domaines politique, économique et culturel. Le droit est plus rarement pris en compte comme outil d'influence dans l'action extérieure des États.Or, le droit joue un rôle fondamental dans la diplomatie économique. En effet, un pays qui n'est pas capable de défendre son système juridique est un pays qui économiquement est en péril, car c'est un pays qui ne peut pas s'exporter.Si la France par exemple, ou d'autres pays, se mettent à la remorque de l'Alternative Dispute Resolution jusque dans leur propre droit interne, ces pays ne pourront plus exporter leur système juridique au risque de ne plus pouvoir exporter tout court. Ils risquent alors de perdre une partie essentielle et substantielle de leur capacité de projection sur la scène internationale.De même, lorsque la francophonie économique perd du terrain, c'est tout un pan de la diplomatie économique qui perd de sa force de frappe.Avec les clauses compromissoires et clauses de médiation inspirées des modèles anglo-saxons qui se répandent dans les contrats internationaux, comment les juridictions des pays francophones qui ont été calquées sur le système judicaire français pourront-elles continuent à exister ? Les arbitres anglo-saxons finiront-ils par imposer lentement mais sûrement la Common law ? Il y a là un enjeu de diplomatie économique énorme.Nous verrons comment défendre au mieux la francophonie économique et juridique en évitant que l'Alternative Dispute Resolution ne devienne le cheval de Troie du droit anglo-saxon, avec à terme, le risque que des systèmes nationaux disparaissent.Ce sont là des questions légitimes et très graves, et l'on peut comprendre qu'elles soient posées avec une certaine persistance.Avec l'élargissement continu du champ des relations internationales, le droit doit devenir l'objet d'une politique extérieure stratégique à part entière. C'est pourquoi nous plaidons pour la mise en place d'une diplomatie juridique française et formulons des recommandations ainsi qu'une stratégie d'influence juridique extérieure.En prenant la défense et en illustrant le droit continental et le droit français dans le droit global à travers les exemples de la médiation et de l'arbitrage international, nous espérons contribuer à l'ébauche d'une théorie de la diplomatie juridique et à ouvrir des pistes nouvelles de réflexion en matière d'influence internationale, en particulier d'influence juridique internationale.Nous espérons contribuer ainsi modestement mais utilement à la défense du droit français et du droit continental pour que la confrontation et la compétition des système juridiques n'aboutissent pas à la domination d'un système juridique sur un autre mais que cette compétition aille au contraire dans le sens d'un meilleur équilibre entre les systèmes juridiques, dans le sens du progrès et de l'amélioration du droit français et du droit continental, mais aussi - s'il se peut -dans le sens des progrès dans la défense des causes et des valeurs universelles. In the traditional conception of diplomacy, the external action of States is confined to the political, economic and cultural domains. Law is more rarely taken into account as a tool of influence in the external action of States.However, Law plays a fundamental role in economic diplomacy. Indeed, a country that is not able to defend its legal system is a country that is economically in danger, because it is a country that cannot be exported. If France, for example, or other countries, follow the Alternative Dispute Resolution right up to their own domestic law, these countries will no longer be able to export their legal system at the risk of no longer being able to export at all. They then risk losing an essential and substantial part of their ability to project themselves on the international scene.Similarly, when the economic Francophonie loses ground, a whole section of economic diplomacy loses its strike force.With arbitration clauses and mediation clauses inspired by Anglo-Saxon models that are spreading in international contracts, how will the courts of French-speaking countries that have been modeled on the French judicial system be able to continue to exist? Will Anglo-Saxon arbitrators end up slowly but surely imposing the Common law? There is a huge stake in economic diplomacy here.We will see how best to defend the economic and legal Francophonie by preventing the Alternative Dispute Resolution from becoming the Trojan horse of Anglo-Saxon law, with the eventual risk that national systems will disappear.These are legitimate and very serious questions, and one can understand that they are asked with a certain persistence.With the continuous widening of the field of international relations, Law must become the object of a strategic foreign policy. This is why we plead for the establishment of a French legal diplomacy and formulate recommendations as well as a strategy of external legal influence.By defending and illustrating continental law and French law in global law through the examples of mediation and international arbitration, we hope to contribute to the sketch of a theory of legal diplomacy and to open new paths of reflection in terms of international influence, in particular international legal influence.We hope in this way to contribute modestly but usefully to the defense of French law and continental law so that the confrontation and competition of legal systems does not lead to the domination of one legal system over another but that this competition goes on the contrary in the sense of a better balance between legal systems, in the direction of progress and improvement of French law and continental law, but also - if possible - in the direction of progress in the defense of universal causes and values.
Keywords: Arbitrage; Arbitragem; Arbitration; Diplomatie; Diplomatie juridique; Diplomatie économique; Droit global; Economic Diplomacy; Global Law; Influence; Influence juridique internationale; International Legal Influence; Legal Diplomacy; MARD; Mediación; Mediation; Mediação; Médiation; Relations extérieures; Relations économiques internationales

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Procedural powers of arbitrators in international arbitration- Real or perfunctory? - Mishra, Ajit Kumar (International Journal of Law, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; International Arbitration; Lex arbitri; Procedural powers; Tribunal power

The Dilemma of International Arbitration Awards in Indonesia - Puspita, Lona; Budiono, Abdul Rachmad; Kusumadara, Afifah; Widagdo, Setyo (International Journal of Social Science Research and Review, 2023)
The final and binding nature of international arbitral awards results in the nullification of the rights of the parties to file legal remedies against the arbitral award, as is the case with decisions of national courts that can be appealed, appealed, or reviewed. However, Article 68 paragraph (2) of Law Number 30 of 1999 concerning arbitration and Alternative Dispute Resolution provides an opportunity for parties who refuse to recognize and implement an international arbitral award that can be appealed to, as well as Article 70 must also be explained that Article this applies only to national arbitrations. This of course creates legal uncertainty, disuse, and injustice for the parties. Therefore, what is highlighted in this research is what is the position of the final and binding international arbitration award in Indonesia. The research method used in this article is legal research using primary and secondary legal materials. The results of the research show that the position of international arbitral awards in Indonesia is not the same as the decisions of national courts because they cannot be appealed, cassated, and reviewed. Therefore, it is necessary to completely amend international arbitration arrangements by removing Article 68 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in order to provide legal certainty, benefit, and justice for the parties.
Keywords: Award; Final and Binding; International Arbitration

L'arbitrage à l'épreuve des procédures belges d'insolvabilité d'entreprises - Dantinne, Rouslan (Université de Liège, 2023)
Alors que deux entreprises sont liées par une convention d’arbitrage, une procédure d’insolvabilité est ouverte en Belgique à l’égard de l’une d’elles. De nombreuses questions émergent : L’instance arbitrale en cours doit-elle être suspendue ? Dans la positive, pourra-t-elle reprendre ? Les pouvoirs de l’arbitre sont-ils impactés ? L’instance n’a pas débuté, la validité de la convention d’arbitrage est-elle compromise ? La convention n’existe pas, les parties peuvent-elles la conclure ? L’entreprise en difficulté perd-elle sa capacité compromissoire ? Cette capacité est-elle transférée au praticien de l’insolvabilité ? La sentence a été rendue, peut-elle être exécutée ? Dans le présent exposé, nous mettons l’arbitrage à l’épreuve des procédures belges d’insolvabilité d’entreprises.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; Faillite; Insolvabilité; Insolvency; Procédures d'insolvabilité; Réorganisation judiciaire

L'unanimité de l'accord de conciliation en droit OHADA : une logique juridique irréaliste ? - Kourouma, Moussa Fanta (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2023)

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Les garanties du procès équitable à l’épreuve des modes alternatifs de règlement de conflits - Guedegbe, Igor Samson Bidossessi (Revue Béninoise des Sciences Juridiques et Administratives, 2023)

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Effective Conflict Management - International Chamber of Commerce (ICC Publication DRS, 2023)

The International Validity of Domestic Law in Investment-Treaty Arbitration - Jarrett, Martin (Arbitration international, 2023)
Keywords: Arbitrage; Arbitragem; Arbitration; Investment arbitration; Investments

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Regards sur l’intervention du juge étatique dans la constitution du Tribunal Arbitral dans l’espace OHADA - Mainibe Tchiombe, Calice Cléopâtre (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
Qu’il soit institutionnel ou adhoc, L’arbitrage est vu comme un mode de règlement des litiges qui a vocation à se dérouler, de la requête initiale à la sentence finale, sans l’intervention du juge étatique. Il arrive, cependant que, ce juge soit amené à intervenir dans le processus arbitral, pour une raison ou pour une autre. On a pu ainsi dire qu’il n’y a pas de bon arbitrage sans un bon juge. Bien que l’intervention du juge étatique doivent rester exceptionnelle en matière d’arbitrage, il importe que ledit juge soit identifié, d’autant qu’il n’est pas le mena selon la phase à laquelle il intervient et peut varier d’une organisation judiciaire à une autre.
Keywords: Juge étatique; Organisation judiciaire

L’encadrement juridique de la médiation dans l’espace OHADA : analyse critique de l’acte uniforme relatif à la médiation - Mukuamu, Prince (Université de Sherbrooke, 2023)
Aujourd'hui plus qu'hier, la médiation suscite l’intérêt tant des chercheurs, des praticiens, que des politiques. Cet intérêt se matérialise notamment par les différents cadres juridiques dont elle bénéficie dans plusieurs législations. Afin de promouvoir la médiation au sein de ses États membres, L’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a adopté le 23 novembre 2017 un Acte Uniforme relatif à la Médiation (AUM). Après avoir adopté depuis plus de deux décennies un Acte uniforme sur l’arbitrage, l’organisation régionale confirme sa volonté de promouvoir les modes alternatifs de règlement de conflits dans le domaine du droit des affaires. Cependant, l’AUM est un instrument juridique particulier attendu qu'il est le premier de son genre à s’appliquer également aux domaines non encore régis par le droit OHADA. Toutefois, si la médiation tend à se développer de plus en plus, il convient de prendre garde à ce que cette évolution, notamment en ce qui concerne son encadrement légal, ne conduise pas à sa dénaturation. Voilà l’un des défis auquel est également soumis le législateur OHADA.
Keywords: AUM; Acte uniforme; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; OHADA

Les principes directeurs du procès équitable en médiation OHADA - Ngono Yakam, Marie Joseph (Revue Africaine des Réflexions Juridiques et Politiques, 2023)
L'image de l’alternative et de la souplesse de la médiation semble aux premiers abords exclure les principes directeurs du procès équitable de ce mode de règlement des conflits. Mais la réalité en est tout autre. Entant qu'instrument de justice, la médiation ne saurait s’affranchir des garanties d’ordre procédurales. Cette survivance va donc de soi puisque tout comme le procès, la médiation fait intervenir un tiers. La présente étude consiste donc à examiner la question des principes du procès équitable appliqués à la médiation OHADA.
Keywords: Fair trial; Guiding principle; MARD; Mediación; Mediation; Mediação; Médiation; OHADA; Principe directeur; Procès équitable

L'arbitrage international dans les contrats publics en droits marocain et français - Raissi, Imane (Revue du Droit Marocain, 2023)
Le recours à l’arbitrage, comme mode de règlement des différends commerciaux internationaux qui s’applique aux contrats publics reliant les Etats et leurs démembrements et avec des investisseurs privés, s’est étendu au fur et à mesure de l’interventionnisme croissant de l’Etat dans l’économie et de la multiplication des leviers juridiques qui lui sont dédiés (marchés publics, gestion déléguée, partenariat public-privé, etc.). Or, ces contrats ainsi soumis à l’hypothèse de l’égalité des parties posent la problématique de l’équilibre entre la portée de la clause compromissoire et la souveraineté des Etats en matière du régime juridique et de la compétence juridictionnelle. Dans une approche comparée entre les Droits marocain et français, cet article analyse les effets du recours à l’arbitrage international sur les règles applicables aux contrats publics à l’origine du différend, notamment, au niveau de la clause attributive de compétence, la compétence juridictionnelle et l’exequatur des sentences arbitrales.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Commande publique; Contrat public; Droit comparé; France; Maroc; Morocco

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

La jurisprudence arbitrale : composante principale du droit international des investissements - Uranga, Paul (Les Cahiers de droit, 2023)
Le droit international des investissements résulte principalement d’une multitude de traités d’investissement, souvent bilatéraux, parfois régionaux et très rarement multilatéraux. Ce régime éclaté, ayant l’arbitrage comme moyen principal de règlement des différends entre investisseurs et État, ne favorise pas, en théorie, l’émergence d’une jurisprudence réellement cohérente et pertinente. Toutefois, la pratique arbitrale florissante en matière d’investissement s’est révélée constituer une véritable jurisprudence à l’importance non négligeable. Bien que le précédent n’ait pas de valeur juridique obligatoire, force est de constater sa valeur persuasive et la systématicité de son usage. Une telle utilisation des précédents arbitraux a pu permettre le développement d’une compréhension commune des normes des traités d’investissement et favoriser ainsi indirectement le développement conventionnel de ce droit. La jurisprudence arbitrale innerve de ce fait tous les pans du droit international des investissements, du discours des arbitres à l’évolution même des normes applicables. C’est en cela que la jurisprudence arbitrale peut s’entendre comme la composante principale du droit international des investissements.

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on.  There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk